Perlindungan Hukum bagi Penjahit Rumahan yang Menerima Pesanan Jahitan dari Perusahaan Garment tanpa Perjanjian Kerja Tertulis - I Made Adi Putrawan; I Nyoman Putu Budiartha; I Putu Gede Seputra (Jurnal Analogi Hukum, 2019)
In the industry in the field of clothing production this can usually be in the form of individuals, convection and garment. In the industry in this field of production there are Laws concerning Labor. Where a Home Tailor has a working relationship with a Garment Company and has a work agreement between the two parties to complete the stitching order that the Garment Company gives to Home Tailors. In the work relationship the Home Tailor (Tailor Fanani) can be mentioned as a Specific Time Worker (PKWT) because the work agreement that has been done is only an oral agreement and only in the form of Down Payment. As for what will be discussed in the discussion include: 1. What is the type of work in the employment relationship between a garment and home tailors, 2. What is the form of legal protection provided by the government for home tailors who work on orders from garment companies without written work agreements. This study is an empirical study analyzed qualitatively descriptive. This data is obtained through interviews with the parties involved in the employment relationship. In the work carried out by the Home Tailor is bulk, where the work given by the Garment Company to these home tailors is a large number and various types of motifs and colors. Legal protection against fanani as a Home Tailor is in preventive and repressive legal protection.